2017
DOI: 10.1530/joe-17-0044
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-383 and miR-146b in different propensities to obesity in male mice

Abstract: The study was designed to investigate the possible mechanisms of hepatic microRNAs (miRs) in regulating local thyroid hormone (TH) action and ultimately different propensities to high-fat diet (HFD)-induced obesity. When obesity-prone (OP) and obesity-resistant (OR) mice were fed HFD for 7 weeks, OP mice showed apparent hepatic steatosis, with significantly higher body weight and lower hepatic TH receptor b (TRb) expression and type 1 deiodinase (DIO1) activity than OR mice. Next-generation sequencing technolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
(40 reference statements)
1
9
0
Order By: Relevance
“…Overall, our results suggest that miR-592 may play an important role in the regulation of hepatic lipid metabolism. Interestingly, a recent study showed that miR-592 was significantly reduced in the liver of mice fed a high-fat-diet for 7 weeks [43], which is consistent our results. However, they further found that miR-592 was not changed in the liver of mice fed a high-fat-diet for 17 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, our results suggest that miR-592 may play an important role in the regulation of hepatic lipid metabolism. Interestingly, a recent study showed that miR-592 was significantly reduced in the liver of mice fed a high-fat-diet for 7 weeks [43], which is consistent our results. However, they further found that miR-592 was not changed in the liver of mice fed a high-fat-diet for 17 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…Notably, the upregulation of miR-146b in obese individuals correlates with a reduction of glucose metabolism and fatty acids mobilization [86]. In line with this observation, miR-146b inhibition in free fatty acids-treated primary hepatocytes displays a decreased accumulation of cellular lipids [85]. Finally, miR-146 exerts a tumor suppressive role in liver cancer cells in vitro and in vivo, through the inhibition of AKT activation mediated by TRAF6 [87].…”
Section: Resultsmentioning
confidence: 97%
“…Intriguingly, ablation of miR-146 in mice leads to severe liver steatosis and hepatitis by the upregulation of TNF-α and IL-6 [82]. Conversely, elevated hepatic level of miR-146b has been found in rats and mice treated with HFD as well as in obese subjects with NAFLD [84,85,86]. Notably, the upregulation of miR-146b in obese individuals correlates with a reduction of glucose metabolism and fatty acids mobilization [86].…”
Section: Resultsmentioning
confidence: 99%
“…For example, mice with a high-fat diet exhibited in the epididymal AT significant downregulation of miR-1247 compared to mice with regular diet [57]. And more, the miR-1247 was upregulated in the liver of obesity-resistant mice compared to prone-obesity subjects raised with high-fat diet [58]. Therefore, the ENSSSCG00000041577 can be the source of miR-1247 that plays a significant role in the counteraction of obesity effects.…”
Section: Validation Of Rna-seq Resultsmentioning
confidence: 99%